Pengaruh Konsentrasi Asam Jawa (Tamarindus indica L.) Terhadap Karakteristik Permen Keras Rendah Kalori - Avista, Nois Brenda; Pratiwi, I Desak Putu Kartika; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Low-calorie hard candy is a type of candy that has a low-calorie content and generally uses sugar substitutes such as stevia and isomalt to provide sweetness without adding significant calories. This research was aimed to determine the effect of tamarind concentration and to obtain the concentration of tamarind which produces low-calorie hard candy with the best characteristics. This study used a completely randomized design with five levels of tamarind concentration, such as 0%, 5%, 10%, 15%, and 20%, with three replications. The variables observed were water content, total acid, total sugar, sensory hedonic test (color, texture, taste, and overall acceptance) and intensity test (stickiness). The data was analyzed by analysis of variance and if the treatment had a significant effect, then it was continued with Duncan multiple range test. The results showed that the concentration of tamarind had a significant effect on water content, total acid, total sugar, color, taste, texture, stickiness and overall acceptance of the hard candy. The best characteristic of low-calorie hard candy was the addition of 5% tamarind with a water content of 0.80%, total acid of 1.02%, total sugar of 24.54%, and sensory color was liked, taste was liked, texture was liked, adhesiveness was slightly non-sticky, vitamin C of 7,56 mg/100g and antioxidant activity of 17.16%.